Concepts of watershed Development and management - Klaij, M.G.; Astatke, A. (Ethiopian Agricultural Research Organization, 2001)
The paper is divided in five major parts. The first part is introduction. The second part deals with watershed degradation and discusses what is to be done. The third part highlights how to optimize water use at a watershed scale. The topic of the fourth section is optimizing agricultural watershed. Essential technical elements of land use productivity and resource protection is discussed in this section. Land capability calssification for watershed management is the point of the last section. At the end of the paper watershed management is defined; objectives of watershed management outlined; farmers' participation in watershed Development examined; and integrated watershed management discussed.